Responsabilidad social territorial: Ejemplo de gobernanza innovadora y competitiva en Alcalá de Guadaíra - Celia Benitez Morales; Maria Lorena Campos Urribarri; José Manuel Vidal Gandul (Atlantic Review of Economics, 2015)
– The Protocol for Socially Responsible Territory is the result of a local sustainability management experience, which has demonstrated the importance of public administration in social innovation. This article describes the process through which such protocol was obtained, its characteristics and its principles as well as the strengths that this protocol offers. The definition of Socially Responsible Territory (TSR) is presented as a contribution to the theoretical development of a new research area, whose prospects are favored by the potential practical effects on public and corporate alliances locally. This protocol offers competitive advantages to governments who are preparing to seize the opportunities from the Europe 2020 Strategy for Growth.
Keywords: M14; R58; R11; 330